Needle tract seeding after percutaneous cryoablation of small renal masses; a case series and literature review. (3rd March 2020) - Rizzo, Michele; Cabas, Paolo; Pavan, Nicola; Umari, Paolo; Verzotti, Enrica; Boltri, Matteo; Stacul, Fulvio; Bertolotto, Michele; Liguori, Giovanni; Trombetta, Carlo
Abstract: Neoplastic cell seeding due to needle tumor manipulation during renal mass biopsy (RMB) or thermal ablative treatment is a rare but potentially serious event that can turn an organ-confined and curable tumor in a nonorgan-confined and non-curable disease. Despite the widespread use of percutaneous thermal ablative treatment for small renal masses (SRMs), this complication has been described in few case reports and small case series and has never been reported after ablative treatment alone. We report a series of two patients that underwent cryoablation for SRMs and developed recurrence along the needle tract. Available knowledge on the controversial topic of tumor seeding following needle manipulation are poor. So far, reporting cases of tumor cell seeding due to needle manipulation is useful to permit a better understanding of this complication.